Identifikasi Deiksis Persona pada Film Pendek Aku dan Mesin Waktu: Kajian Pragmatik - Nasution, Muhammad Muslim; Izar, Julisah; Chotimah, Khusnul (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aimed to identify persona deixis in the short film entitled "Aku dan Mesin Waktu. Deixis is words that take meaning from the speech situation, whether in the form of person, time or place) when the words are used. The method in this research used a qualitative descriptive approach. The data collection technique in this research used the listening and note-taking technique, while the data analysis technique in this research used data transcription procedures, data classification, data analysis and drawing conclusions. The results of this research found first person deixis (Aku/-ku, me, me, I and kita), second person deixis (Kamu/-mu, lo, and Mereka), third person deixis (Dia, Nya, and Mereka). ). The most dominant person deixis is first person deixis.